The use of an acetoacetyl‐CoA synthase in place of a β‐ketothiolase enhances poly‐3‐hydroxybutyrate production in sugarcane mesophyll cells. Issue 5 (23rd December 2014) - McQualter, Richard B.; Petrasovits, Lars A.; Gebbie, Leigh K.; Schweitzer, Dirk; Blackman, Deborah M.; Chrysanthopoulos, Panagiotis; Hodson, Mark P.; Plan, Manuel R.; Riches, James D.; Snell, Kristi D.; Brumbley, Stevens M.; Nielsen, Lars K.
Summary Engineering the production of polyhydroxyalkanoates (PHAs) into high biomass bioenergy crops has the potential to provide a sustainable supply of bioplastics and energy from a single plant feedstock. One of the major challenges in engineering C4 plants for the production of poly[(R)‐3‐hydroxybutyrate] (PHB) is the significantly lower level of polymer produced in the chloroplasts of mesophyll (M) cells compared to bundle sheath (BS) cells, thereby limiting the full PHB yield‐potential of the plant. In this study, we provide evidence that the access to substrate for PHB synthesis may limit polymer production in M chloroplasts. Production of PHB in M cells of sugarcane is significantly increased by replacing β‐ketothiolase, the first enzyme in the bacterial PHA pathway, with acetoacetyl‐CoA synthase. This novel pathway enabled the production of PHB reaching an average of 6.3% of the dry weight of total leaf biomass, with levels ranging from 3.6 to 11.8% of the dry weight (DW) of individual leaves. These yields are more than twice the level reported in PHB‐producing sugarcane containing the β‐ketothiolase and illustrate the importance of producing polymer in mesophyll plastids to maximize yield. The molecular weight of the polymer produced was greater than 2 × 106 Da. These results are a major step forward in engineering a high biomass C4 grass for the commercial production of PHB.